Identification of the aroma-active constituents of the essential oils of Water Dropwort (Oenanthe javanica) and ‘Kacip Fatimah’(Labisia pumila) - Pattiram, P. D.; Olusegun, Lasekan; Tan, Chin Ping; Sarker, Md. Zaidul Islam (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The chemical constituents of the essential oils from the leaves of Oenanthe javanica (Water Dropwort) and Labisia pumila (‘Kacip Fatimah’) were established by GC-FID and GC-MS analysis. A total of 41 compounds were each identified in oils of both of ‘Kacip Fatimah’ and Water Dropwort. The compounds obtained from the oil of Water Dropwort were richer in sesquiterperpenes such as α-Copaene (18.3%), Z-Caryophyllene (0.34%) α-Cuprenene (0.40%) and Cembrene-type diterpenes such as Incensole (26.4%) and Cembrenol (0.45%). However, essential oil obtained from ‘Kacip Fatimah’ was predominated with sesquiterpenes alcohols such as Longiborneol (4.83%), Geranyl linalool (3.90%) and T-Cadinol (24.78%). Other significant constituents of the oil from ‘Kacip Fatimah’ were the diterpenes alcohol, Isoabienol (7.89%), β-Santalol acetate (9.35%) and 1, 4-trans-6-methoxyliso-calamene (13.75%).